Left Ventricular Pseudoaneurysm in a Patient With an Apical Aneurysm - Patel, Pratik (JACC Case Rep, 2020)
Left ventricular pseudoaneurysm is a potentially life-threatening complication of acute myocardial infarction. Timely diagnosis is crucial to improve the patient’s prognosis. We describe a multimodality diagnostic approach with emphasis on cardiac magnetic resonance imaging for a left ventricular pseudoaneurysm found surreptitiously in 72-year-old man 2 weeks following an acute myocardial infarction. (Level of Difficulty: Beginner.)